Peran WhatsApp Group Dalam Mendorong Kewirausahaan Masyarakat Modern - Ria Yuni Lestari; Mayang Sari; Tubagus Faai Faujan; Ahyani; Ahmad Zidni Hudaya; Mohamad Firdaus; Idzma Nuraini; Desi Nurafiyani; Supiati (Samudra Publisher, 2025)
Penilitian ini menganalisis peran WhatsApp Group